CGIAR Food Systems Accelerator: agri-innovation report for East and Southern Africa - cohort 2 - Nkosi, Mahlatse; Dlamini, Jerry; Birachi, E.; Dirwai, Tinashe Lindel; Giombini, V.; Ires, Idil; Mhlanga, B.; Munthali, J.; Njiru, A.; Nortje, Karen; Nowak, Andreea C.; Peterson, N.; et al. (International Water Management Institute (IWMI), 2024)
The CGIAR Food Systems Accelerator Agri-Innovation Report for East and Southern Africa: Cohort 2 presents the outcomes of an initiative aimed at transforming agrifood systems across the region. This report documents the journey of ten agribusinesses selected for support under the Ukama Ustawi initiative, which promotes sustainable, climate-smart, and investment-ready agricultural innovations.